2019
DOI: 10.1002/alr.22368
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal prelacrimal approach to the inferior intraconal space: a feasibility study

Abstract: BackgroundEndonasal access to the inferomedial and inferolateral intraconal space via the orbital floor has not been reported. The primary purpose of this study was to assess the feasibility of accessing the inferior intraconal space through the orbital floor via a transnasal prelacrimal approach. Secondarily, it aims to highlight anatomical relationships of neurovascular structures in this space, as a requirement to prevent complications.MethodsSix cadaveric heads (12 sides) were dissected using a transnasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…19 Both the foramen rotundum and foramen ovale could be sufficiently exposed via a transnasal prelacrimal approach. [12][13][14][15][16][17] Therefore, the distal aspect of the anterolateral triangle, which is enclosed by V 2 (foramen rotundum) and V 3 (foramen ovale), providing a direct avenue and the rationality for exposure of the floor of MCF via a prelacrimal approach. 5 The average area of the MCF window was 554.12 AE 60.22 mm 2 , which was adequate for maneuverability into the floor of MCF through this corridor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Both the foramen rotundum and foramen ovale could be sufficiently exposed via a transnasal prelacrimal approach. [12][13][14][15][16][17] Therefore, the distal aspect of the anterolateral triangle, which is enclosed by V 2 (foramen rotundum) and V 3 (foramen ovale), providing a direct avenue and the rationality for exposure of the floor of MCF via a prelacrimal approach. 5 The average area of the MCF window was 554.12 AE 60.22 mm 2 , which was adequate for maneuverability into the floor of MCF through this corridor.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Despite the average area of the bony prelacrimal window was 441.84 AE 37.75 mm 2 after partial removal of the medial and anterior walls of the maxillary sinus, the authors recognized that it was still a challenge to simultaneously manipulate the rod-lens endoscope and 2 instruments through the prelacrimal window. 16 The addition of an anterior antrostomy such as a Caldwell-Luc approach or any other variant, including expanding the prelacrimal window laterally, could obviate the restriction for instrumentation. 30 However, removal of the piriform crest and anterior face of the maxillary sinus, and displacement of the nasolacrimal duct as required to facilitate or expand the prelacrimal corridor, may carry the risk of postoperative piriform aperture stenosis, alar constriction, and epiphora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Li et al 17 included dissection of five cadaveric heads and demonstrated the role of the prelacrimal recess as direct access from the posterolateral maxillary sinus to the lateral recess of the sphenoid sinus, utilising the infra-orbital nerve as a landmark to preserve the vidian nerve and pterygopalatine ganglion. In another cadaveric study by Li et al, 18 the prelacrimal recess was used to access the inferior intraconal space through the orbital floor.…”
Section: Discussionmentioning
confidence: 99%
“…15 Others have suggested the use of endonasal approaches to the orbit. [16][17][18] On previous cadaveric studies, partial resection of the orbital floor via a transnasal prelacrimal approach provided a corridor to access the inferior intraconal space, 16,17 and a transethmoidal approach was advocated to access the superomedial intraconal space. 18 Although both the transethmoidal and prelacrimal approaches can access the inferomedial intraconal space, technical nuances, advantages and drawbacks for each approach have not been sufficiently explored.…”
Section: Introductionmentioning
confidence: 99%